A Qualitative Study of Instructional Coaching Based on an Analysis of Interviews from Teachers, Coaches, and Administrators - (:unkn) unknown (My University, 2017)
The “transfer of training problem” refers to the difficulty professionals have in adopting evidence-based practices after they receive training on those practices. This “transfer of training” problem is especially important to consider for educational professionals in urban settings where students are more likely to not meet grade level academic expectations and where teachers often report feeling underprepared to teach in diverse, dynamic classrooms. Instructional coaching is a type of ongoing, job-embedded professional development that may help teachers overcome the “transfer of training” problem. This study examines exit interview data from teachers, instructional coaches, and administrators who participated in pilot programs of instructional coaching to improve student literacy in four urban schools. Data analysis was completed using a constant comparison approach; 39 salient themes were identified which were then compared to a model of instructional coaching which has been developed based on the existing coaching literature. Considerable support for previous findings concerning instructional coaching was found, based on the qualitative analysis of the interviews, and new factors that contribute to effective coaching were identified. Overall, participants reported positive perceptions of their involvement with instructional coaching, and reported positive outcomes for both students and teachers as a result of the instructional coaching pilot programs. The need for increased teacher decision-making and collaboration in instructional coaching, the application of instructional coaching in urban settings, and the relationship of instructional coaching to school psychologists are discussed.
Keywords: Constant Comparison Approach; Instructional Coaching; Literacy Coaching; Model of Coaching; School Psychology; Urban Education